CHANGES IN THE SPECIES COMPOSITION, STAND STRUCTURE AND ABOVEGROUND BIOMASS OF A LOWLAND DIPTEROCARP FOREST IN SAMBOJA, EAST KALIMANTAN - Krisnawati, Haruni; Wahjono, Djoko; Imanuddin, Rinaldi (Indonesian Journal of Forestry Research, 2011)
The dynamics of species composition, stand structure and aboveground biomass were studied over a 4.3-yr period (December 2004 â April 2009) in a lowland dipterocarp forest of Samboja, East Kalimantan. This study was conducted in six permanent sample plots (100 m x 100 m each) distributed over an area of 26.5 ha of Samboja Research Forest. All woody plants = 10 cm dbh (diameter at 1.3 m aboveground) were identified. In December 2004, 2.143 trees were measured in the six plots, consisting of 39 families, 82 genera and 111 species. The condition in April 2009 (after 4.3 yr) was: 2,466 trees, 40 families, 86 genera and 123 species. Most species were found in both occasions. Fourteen new species were registered, which contributed to 9.8% of a net addition of the total number of species found in the six plots. Over the 4.3-yr period, there was also an increase of 15.1% in density, 12.9% in basal area, and 11.6% in aboveground biomass, respectively. The density increased from 357 to 411 trees per ha; the basal area increased from 20.09 to 22.67 m2 ha-1; and the aboveground biomass increased from 286.3 to 319.4 ton ha. The family Dipterocarpaceae was the richest in species (more than 20 species found in both occasions), followed by Euphorbiaceae, Burseraceae, Fabaceae, and Anacardiaceae (more than five species). Most genera (80%) contained just one species, but Shorea with 13 species was the richest. Four families (Dipterocarpaceae, Fabaceae, Myrtaceae and Lauraceae) contained more than 80% of the aboveground biomass in both occasions (75% of them from Dipterocarpaceae family). The increases in species richness and density did not cause any significant differences in the diversity index and diameter distribution. This condition suggested that forest vegetation of the study site maintains its diversity composition and structural features over the period of study.